DLTS characterisation of defects in III-V compound semiconductors grown by MBE - Mari, Ruaz Hussain (2011)
The interest in the growth of III-V compound semiconductors such as GaAs and AlGaAs on high index planes has increased tremendously over the last few years. The structural, optical and electrical properties III-V based structures are found to improve by, growing on (nil) planes. For example the amphoteric nature of silicon (Si) facilitates the Molecular Beam Epitaxy (MBE) growth of p-type GaAs/AlGaAs heterostructures on (311)A that have higher hole mobilities than those based on the conventional Be-doped p-type on (100) GaAs plane. The incorporation of intentional impurities, such as Si or Be in III-V semiconductors, have desirable effects in terms of controlling the electrical conductivity of the materials. However, other unintentionally incorporated impurities and defects have deleterious effects on the electrical and optical properties of III-V based devices. In this thesis, current-voltage-temperature (I-V-T), capacitance-voltage (C-V) Deep Level Transient Spectroscopy (DLTS) and Laplace DLTS techniques have been used to investigate defects in several MBE III-V epilayers and modulated structures grown both on the conventional (100) and non-(100) GaAs substrates. These include: (i) n-type silicon-doped (n11)B (n = 2-5) GaAs epitaxial layers; (ii) n-type silicon-doped (100) and (311)B GaAs/AlGaAs multi-quantum well (MQW); (iii) n-type silicon-doped (100) MQWs grown at different substrate temperatures, arsenic overpressures and arsenic species (As2 and As4); (iv) p-type Be-doped (100) and (311)A AlGaAs epitaxial layers; (v) GaAs/AlGaAs two dimensional electron gas (2DEG); (vi) commercially grown high electron mobility transistors (HEMT).